A review of diagnostic accuracy and clinical impact from the focused use of perioperative ultrasound. - Bainbridge, D; McConnell, BM; Royse, C (Can J Anaesth., 2018)
Purpose: To perform a narrative review of the current trials examining the use of perioperative ultrasound to diagnose common issues related to the heart, lungs, stomach, and airway. Method: A review of the current literature was conducted in June 2017 on all trials involving ultrasound, including both surface and transesophageal ultrasound, in the perioperative period. The search included the terms 'ultrasonography', 'perioperative care', 'point-of-care', and 'bedside'. Trials were limited to human subjects with no language or time restrictions being applied. The results were then collected and a narrative review was completed with the available information. Results: In total 1,176 reports of original investigation or systematic reviews were collected and reviewed. Of those 1,176 reports and reviews, a total of 80 original articles met the inclusion criteria for this review. Topics were broadly defined based on common themes emerging from the literature including cardiac disease, lung pathology (pneumothorax, pleural effusion, pulmonary edema, and pulmonary consolidation), volume and contents of the stomach, confirmation of endotracheal tube position, confirmation of lung isolation, and the application of ultrasound for guiding cricothyroidotomy. Where possible, the sensitivity and specificity of the trials are presented. Few trials reported on patient outcomes, although several discussed provider outcomes such as a change in anesthesia practice. In addition, trials reporting outcomes, although few in number, were included. Conclusion: Perioperative point-of-care ultrasound is a useful method for the diagnosis of many important perioperative conditions. The impact of this diagnostic approach on patient outcomes however remains to be determined.